SEX-RAR : the Rapid Assessment and Response Guide on Psychoactive Substance Use and Sexual Risk Behaviour. (World Health Organization, 2002)
This guide provides practical guidance on the use of Rapid Assessment and Response (RAR), a method specially designed to generate information that can help the planning and development of health policies and programmes as well as specific health interventions and services. The guide is designed for use by organizations and groups that wish to plan and carry out an assessment of the relationship between substance use and risk behaviour in the population of a particular area, in order to develop or expand the activities for promoting health and preventing harm, as well as to develop programmes f.